Capital Utilization and the Foundations of Club Convergence - Carl-Johan Dalgaard; Jes Winther Hansen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2004)
Club convergence may arise as an empirical prediction from standard neoclassical growth models where the aggregate production technology displays diminishing returns to capital. This requires that the propensity to save from wage income is greater than the propensity to save from capital income. This paper shows how endogenous capital utilization may produce such savings behavior in an otherwise standard Solow model. That is, even if households save a constant fraction of total income multiple stable steady states may arise when capital utilization is endogenously determined.
Keywords: O10; O41; 330; economic growth; capital utilization; multiple eqilibria; Kapazitätsauslastung; Entwicklungskonvergenz; Wachstumstheorie